Konsep Hak Kepemilikan Berdasarkan Hukum Adat Dan Hukum Islam - Yanto Sufriadi (Syiar Hukum, 2021)
This study focuses on the concept of land ownership rights based on Indonesian customary law and Islamic law. This study is a normative legal research with the approach of statutory law, customary law and Islamic law. Data obtained through library research. Based on this study, it is concluded that both Indonesian Customary Law and Islamic Law recognize individual ownership of land, but that ownership has a social function, namely that land rights must provide benefits for welfare, both the welfare of the owner and the welfare of the community. Both Indonesian Customary Law and Islamic Law prohibit land ownership that is detrimental to the welfare of others. This concept is expected to become a reference in formulating the ownership of material rights in Indonesian National Law.